Design of rectangular dielectric resonator antenna using glass added Barium Strontium Titanate - Tripathi P.; Kumari P.; Parkash O.; Kumar D.; Sahu B.; Singh S.P. (My University, 2025)
A compact aperture-coupled dual segment rectangular dielectric resonator antenna (ACDS-RDRA) is described in this paper. The antenna consists of Teflon (ϵr = 2.1) as lower segment and liquid phase (glass) sintered Barium Strontium Titanate (BST) namely Ba0.5Sr0.5TiO3 (ϵr = 27) as upper segment. 10 wt% of PbO-BaO-B2O3-SiO2 glass was added to lower the sintering temperature from 1050 °C to 800 °C and increase the dielectric constant of BST. The input and radiation characteristics of ACDS-RDRA are investigated through simulation using Ansys HFSS software. The antenna provides the simulated input impedance bandwidth of 690 MHz (8.80 - 9.49 GHz) with a simulated peak gain of 6.63 dB at 9.1 GHz. The antenna provides broadside radiation patterns in both E-and H-planes of the antenna with fairly low cross-polarization levels in E-plane were obtained. Such RDRA can find potential applications in radar and satellite communication. © 2015 IEEE.